A three-dimensional nano-porous foam catalyst Fe2O3@N-rGF easy to recycle and a preparation method and application thereof
Patent Information
- Application Number
- CN202611186324.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-16
AI Technical Summary
例如,Nie等人报道,经过5次循环后,MCC/Cu2O/GO复合泡沫的亚甲基蓝降解率由77.9%降至41.1%,SEM显示三维多孔结构发生明显塌陷,GO纳米片出现褶皱,表明其微观结构完整性与活性维持能力不足
(1)在制备方法方面,本发明以Fe(NO3)3·9H2O为铁源、GO为碳前驱体、尿素为氮源、造孔剂和均相沉淀剂,通过一步水热法同步实现三维泡沫结构的构建、氮掺杂及Fe2O3纳米颗粒的均相沉淀与均匀锚定,制备工艺简便。该方法克服了传统方法需分步进行造孔、杂原子掺杂和金属负载的工艺复杂问题。所制得的催化剂以N-rGF为三维互连多孔骨架,兼具高比表面积与发达的介孔结构;Fe2O3纳米颗粒平均粒径约43.02 nm,通过均相沉淀的方法锚定于N-rGF的表面及孔道内壁,未出现团聚现象;Fe元素相对含量达13.08%。上述特征共同实现了活性组分的高负载量、纳米级尺寸控制与均匀分散,克服了现有合成方法难以兼顾上述三个目标的技术瓶颈。对比实验表明:若不添加GO(即仅以Fe(NO3)3·9H2O和尿素进行水热反应),所得Fe2O3颗粒出现明显团聚;若以强碱(如NaOH)替代尿素作为沉淀剂,则所得Fe2O3呈大尺寸条状结构。
Smart Images

Figure CN122912897A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of environmental catalytic materials and advanced oxidation water treatment technology, and particularly relates to an easily recyclable three-dimensional nanoporous foam catalyst Fe2O3@N-rGF, its preparation method and application. Background Technology
[0002] With the acceleration of industrialization and urbanization, recalcitrant pollutants such as bisphenol A (BPA) and endocrine disruptors are frequently detected in water bodies, posing a potential threat to the ecological environment and human health. Traditional biodegradation and physical adsorption processes are insufficient for the effective removal of these pollutants. Advanced oxidation processes (AOPs) can generate sulfate radicals (SO4· ... - Active species with high oxidation potentials, such as hydroxyl radicals (·OH), are highly efficient at oxidizing recalcitrant new pollutants in water, thus finding widespread application in water treatment. Currently, the catalytic / activation methods for active organic compounds (AOPs) are mainly divided into homogeneous catalysis and heterogeneous catalysis. Compared to homogeneous catalysis, heterogeneous catalysis utilizes solid catalysts to achieve stable dispersion and exposure of active sites, overcoming the dependence of homogeneous systems on dissolved metal ions, and typically has a wider applicable pH range. These advantages make it significant in broadening catalytic reaction conditions and enhancing its engineering application potential, and it has become a major research direction in this field.
[0003] Currently, heterogeneous catalysts are mainly metal-based and carbon-based materials. Carbon-based catalysts generally have good chemical stability, but relatively low catalytic activity; metal-based catalysts have high activity, but pose a risk of metal ion leaching. More importantly, although the chemical composition and structure of the above two types of materials have been continuously optimized, they mostly exist in powder form, which is not easy to recover in practical applications and is prone to loss, thus increasing environmental risks. Preparing foam catalysts by loading metal active components onto three-dimensional porous carbon-based supports is one of the effective strategies to solve these problems. The foam catalysts obtained by this strategy combine the stability of carbon-based supports with the high catalytic activity of metal components. Furthermore, their macroscopic bulk morphology allows for effective recovery through simple mechanical means (such as direct clamping), and the metal-support interface interaction helps to inhibit metal ion leaching, reducing environmental risks. Current research has already been conducted in this direction. For example, Nie et al. (J. Nie et al., Fabrication of MCC / Cu2O / GO composite foam with high photocatalytic degradation ability toward methylene blue, Carbohydr. Polym.(2019, 223, 115101) Cu2O particles were blended with graphene oxide (GO) in a microcrystalline cellulose (MCC) matrix to prepare an MCC / Cu2O / GO composite foam. This foam, thanks to its three-dimensional porous structure and the synergistic effect of the Cu2O / GO composite, achieved effective photocatalytic degradation of methylene blue (degradation rate of 83.62 mg / (mg·h)), and maintained macroscopic bulk integrity after five cycles, allowing for rapid recovery via direct clamping. Similarly, Zhou et al. (Q. Zhou et al., Persulfate-enhanced removal of bisphenol A by copper oxide / reduced graphene oxide foam: Influencing factors, mechanism and degradation pathway) Chemosphere (2023, 340, 139786) CuO nanosheets were anchored in three-dimensional reduced graphene oxide foam (RGF) to obtain CuO / RGF composite foam. This material not only significantly improved the degradation rate constant of BPA (0.00917 min) by activating persulfate (PDS), but also... -1 The leaching rate of Cu(II) was 1.24 times that of pure CuO and 6.46 times that of pure RGF, respectively. More importantly, the three-dimensional network structure of RGF effectively inhibited the leaching of Cu(II) (the leaching amount was only about 44% of that of the pure CuO system), and the total removal rate remained at about 82% after five uses, and the material could be directly picked up and recycled.
[0004] The above studies demonstrate that the supporting strategy can impart a macroscopic bulk morphology to the catalyst and suppress metal ion leaching, showing its potential to solve the aforementioned problems. Nevertheless, existing supported foam catalysts still face the following fundamental challenges: (1) How to control the particle size to the nanoscale and achieve uniform dispersion while increasing the loading of metal active components is a bottleneck that needs to be overcome in existing synthesis methods. For example, in Nie et al.'s system, Cu2O particles formed spherical agglomerates (average diameter up to 2.3 μm), resulting in a significant deficiency in the utilization rate of effective active sites (removal rate of 77.9%). In Zhou et al.'s system, CuO nanosheets were dispersed in RGF support, but their size was still at the micrometer level (length about 2.1 μm, width about 500-600 nm), the dispersion was severely uneven, and the loading was only 2.5 wt%, resulting in a small number and low density of active sites, and the catalytic efficiency was significantly limited (removal rate of 86.10%).
[0005] (2) Maintaining the integrity of the microstructure and the persistence of catalytic activity of composite foam during recycling is a significant challenge for existing materials. For example, Nie et al. reported that after 5 cycles, the methylene blue degradation rate of MCC / Cu2O / GO composite foam decreased from 77.9% to 41.1%, and SEM showed that the three-dimensional porous structure collapsed significantly and GO nanosheets became wrinkled, indicating insufficient microstructure integrity and activity maintenance. In contrast, Zhou et al.'s system maintained a removal rate of only about 82% after 5 cycles.
[0006] Therefore, how to further increase the loading of metal active components and achieve their nanoscale uniform dispersion while maintaining the inherent advantages of foam catalysts such as easy recycling and suppression of metal ion leaching to reduce environmental risks, and ensuring the integrity of the microstructure and the persistence of catalytic activity during recycling, is a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0007] This invention provides an easily recyclable three-dimensional nanoporous foam catalyst, Fe2O3@N-rGF, its preparation method, and its applications. The catalyst is prepared via a one-step hydrothermal method using Fe(NO3)3·9H2O as the iron source, GO as the carbon precursor, and urea as the nitrogen source, pore-forming agent, and homogeneous precipitant. This method simultaneously achieves the construction of a three-dimensional foam structure, nitrogen doping, and in-situ growth and uniform anchoring of nanoscale Fe2O3 particles under hydrothermal conditions. The catalyst exhibits a macroscopic bulk morphology, is easily recyclable, and can be used to activate PDS to degrade novel pollutants in water, such as bisphenol A (BPA).
[0008] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a method for preparing a three-dimensional nanoporous foam catalyst Fe2O3@N-rGF, comprising the following steps: Fe(NO3)3·9H2O and urea (urea also serves as a nitrogen source, pore-forming agent and homogeneous precipitant) were mixed evenly to obtain an iron precursor solution, which was then mixed with a graphene oxide (GO) dispersion to obtain a mixed solution. The mixture is transferred to a hydrothermal reactor for a one-step hydrothermal reaction. After the reaction was completed, the product was washed and dried to obtain the three-dimensional nanoporous foam catalyst Fe2O3@N-rGF.
[0009] Furthermore, the concentration of the graphene oxide dispersion is 2 g / L.
[0010] Furthermore, the concentration of Fe(NO3)3·9H2O in the iron precursor solution is 0.2 M to 0.5 M; preferably 0.3 M.
[0011] Further, the volume ratio of the GO dispersion to the iron precursor solution is (4.5~11.5):0.5; preferably 6.5:0.5.
[0012] Furthermore, the reaction temperature of the one-step hydrothermal reaction is 120~210℃, and the reaction time is 12~24 h; preferably, the reaction temperature is 180℃ and the reaction time is 12 h.
[0013] Furthermore, the washing is performed by washing with deionized water until neutral, and the drying is performed by natural air drying.
[0014] Furthermore, the GO dispersion is prepared from natural flake graphite using a modified Hummers process.
[0015] The present invention also provides an easily recyclable three-dimensional nanoporous foam catalyst Fe2O3@N-rGF prepared according to the above preparation method.
[0016] The catalyst prepared in this invention is a bulk three-dimensional nanoporous foam material, with nitrogen-doped reduced graphene oxide foam (N-rGF) forming a three-dimensional interconnected porous network framework, exhibiting high specific surface area and well-developed mesoporous structure. Fe2O3 nanoparticles are uniformly anchored on the surface and inner walls of the pores of N-rGF through homogeneous precipitation, achieving high dispersion and stable loading of the active components. The nitrogen doping forms in the N-rGF include pyridine nitrogen, pyrrole nitrogen, graphitic nitrogen, and nitrogen oxides (NOx). X ) species. Among them, nitrogen species containing lone pairs of electrons, such as pyridine nitrogen and pyrrole nitrogen, can form strong coordination with Fe2O3 nanoparticles, thereby significantly enhancing the anchoring stability of the active components on the carbon framework and effectively inhibiting the leaching of metal ions.
[0017] The present invention also provides an application of the above-mentioned easily recyclable three-dimensional nanoporous foam catalyst Fe2O3@N-rGF in the degradation of new pollutants in water by activated persulfate (PDS), wherein the new pollutants include at least one of BPA, bisphenol F (BPF), and bisphenol S (BPS).
[0018] Furthermore, the concentration of the organic pollutants in the water is 0.5~14 mg / L, and the concentration of the PDS in the water is 0.3~1.8 mM.
[0019] Furthermore, the degradation is carried out in water with a pH of 3.0 to 11.0.
[0020] Furthermore, the water body is deionized water, tap water, river water, or effluent from a sewage treatment plant.
[0021] Furthermore, after the catalyst activates the PDS to degrade pollutants, it can be recovered and reused through simple separation.
[0022] Compared with the prior art, the present invention has the following advantages and technical effects: (1) Regarding the preparation method, this invention uses Fe(NO3)3·9H2O as the iron source, GO as the carbon precursor, urea as the nitrogen source, pore-forming agent, and homogeneous precipitant. A one-step hydrothermal method is used to simultaneously construct a three-dimensional foam structure, perform nitrogen doping, and achieve homogeneous precipitation and uniform anchoring of Fe2O3 nanoparticles. The preparation process is simple. This method overcomes the complex process of traditional methods that require step-by-step pore-forming, heteroatom doping, and metal loading. The resulting catalyst uses N-rGF as a three-dimensional interconnected porous framework, possessing both high specific surface area and well-developed mesoporous structure. The average particle size of the Fe2O3 nanoparticles is approximately 43.02 nm. They are anchored to the surface and inner walls of the pores of N-rGF through homogeneous precipitation without agglomeration. The relative Fe content reaches 13.08%. These characteristics collectively achieve high loading of active components, nanoscale size control, and uniform dispersion, overcoming the technical bottleneck of existing synthesis methods that struggle to achieve these three objectives simultaneously. Comparative experiments show that if GO is not added (i.e., only Fe(NO3)3·9H2O and urea are used for hydrothermal reaction), the resulting Fe2O3 particles show obvious agglomeration; if a strong alkali (such as NaOH) is used instead of urea as a precipitant, the resulting Fe2O3 has a large-sized strip structure.
[0023] (2) In terms of catalytic performance, the Fe2O3@N-rGF catalyst of the present invention, under the conditions of 0.018 g dosage and 0.6 mM PDS concentration, achieved a 90-minute removal rate of 96.94% for 5 mg / L BPA, which is 2.75 times that of Fe2O3, 2.22 times that of reduced graphene oxide foam (rGF), and 1.43 times that of N-rGF; the degradation rate constant is 0.0219 min. -1 The efficiency of the Fe2O3@N-rGF catalyst was 13.7 times that of Fe2O3, 14.6 times that of rGF, and 3.22 times that of N-rGF, respectively. After five cycles, the removal rate of BPA by PDS activated by the Fe2O3@N-rGF catalyst remained above 90%, with no significant degradation of the material structure or performance, demonstrating excellent structural integrity and cycle stability. This solved the problem of structural collapse and activity decline in existing foam catalysts during recycling.
[0024] (3) Regarding environmental safety, thanks to the strong coordination between nitrogen species containing lone pairs of electrons, such as pyridine nitrogen and pyrrole nitrogen in N-rGF, and Fe2O3 nanoparticles, this invention significantly enhances the anchoring stability of the active components on the carbon skeleton at the chemical bonding level, effectively inhibiting the leaching of metal ions. The highest leaching amount of iron ions in the solution after the reaction is only 0.0728 mg / L (at pH=3.0), which is far below the first-level discharge limit (≤0.5 mg / L) stipulated in the National Integrated Wastewater Discharge Standard (GB 8978-1996), effectively reducing environmental risks.
[0025] (4) In practical applications, the Fe2O3@N-rGF catalyst of this invention, when used to activate PDS to degrade BPA, achieves a BPA removal rate of over 90% within a wide pH range of 3.0 to 11.0. In various actual water bodies, including deionized water, tap water, river water, and wastewater treatment plant effluent, the catalyst achieves a BPA removal rate of over 96%, demonstrating its applicability and resistance to interference in complex aquatic environments. Furthermore, the catalyst also exhibits good degradation effects on other novel pollutants such as BPF and BPS, demonstrating broad applicability to a wide range of pollutants.
[0026] In summary, the Fe2O3@N-rGF catalyst prepared in this invention possesses high activation performance, structural stability, adaptability to wide pH range and complex water quality, low risk of metal ion leaching, and easy recovery due to its macroscopic bulk nature. This catalyst effectively overcomes the difficulties in recovery and environmental risks associated with traditional powder catalysts. It also breaks through the bottlenecks of existing supported foam catalysts in controlling material structure to achieve high loading of active components, nanoscale size, and uniform dispersion, as well as the defects of microstructure collapse and insufficient catalytic activity persistence during recycling. Therefore, it provides a high-performance, environmentally friendly catalytic material for removing new pollutants from water based on persulfate advanced oxidation technology. Attached Figure Description
[0027] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings: Figure 1 The results show the performance test results of the Fe2O3@N-rGF catalysts obtained with different concentrations of Fe precursor in Examples 1-4 for activating PDS to degrade BPA (different concentrations correspond to the concentrations of Fe precursor solutions in different examples, 0.2 M represents Example 1, and so on). Figure 2The results show the performance of Fe2O3@N-rGF catalysts prepared with different volumes of GO dispersion in Examples 5-8 in activating PDS to degrade BPA (different volumes correspond to the amount of GO dispersion used in different examples, 4.5 mL represents Example 5, and so on). Figure 3 The figures show the performance test results of Fe2O3@N-rGF catalysts prepared at different hydrothermal temperatures in Examples 9-12 for activating PDS to degrade BPA. The inset is a picture of the actual object (different temperatures correspond to different hydrothermal reaction temperatures in different examples, 120℃ represents Example 9, and so on). Figure 4 The figures show the performance test results of Fe2O3@N-rGF catalysts prepared at different hydrothermal reaction times in Examples 13-16 for activating PDS to degrade BPA. The inset is a picture of the actual object (different times correspond to different hydrothermal reaction times in different examples, 12h represents Example 13, and so on). Figure 5 The blocky three-dimensional nanoporous foam catalyst Fe2O3@N-rGF prepared under the optimal conditions (hydrothermal reaction temperature 180℃, reaction time 12 h, Fe precursor solution concentration 0.3 M, GO dispersion volume 6.5 mL) is shown in the images (a), scanning electron microscope images (b, c, inset in c is the particle size distribution of Fe2O3 in Fe2O3@N-rGF), energy dispersive spectroscopy (d), and high-resolution transmission electron microscope images (e, f) at different resolutions. Figure 6 The images show scanning electron microscope (SEM) images at different magnifications of the materials obtained in Comparative Example 1 (a) without GO, Comparative Example 2 (b) with NaOH instead of urea as the precipitant, and the material prepared under the optimal conditions of this invention (c). The insets show the particle size distribution of Fe2O3 in each material. Figure 7 The results are the performance test results of the Fe2O3@N-rGF catalyst activated in Example 17 for the degradation of BPA by PDS in cycles 1 to 5. Figure 8 The results of the performance test of Fe2O3@N-rGF catalyst in PDS degradation of BPA under different pH conditions in Examples 18-22 are shown in (a) and Fe ion leaching amount (b) (different pH values correspond to different examples, pH 3.00 corresponds to Example 18, and so on). Figure 9 The results are the performance test results of Fe2O3@N-rGF catalyst in Examples 23-25 for activating PDS to degrade BPA in tap water, river water and sewage treatment plant effluent; Figure 10The results of the performance test of Fe2O3@N-rGF catalyst in Examples 26-27 for PDS degradation of BPF and BPS are shown in (a) and the corresponding degradation rate constant (b). Figure 11 The results of the performance tests (a) and the corresponding degradation rate constants (b) of the control materials Fe2O3, rGF, N-rGF in Comparative Examples 3-5 and the Fe2O3@N-rGF catalyst prepared in Example 28 of this invention for activating PDS to degrade BPA are shown. Detailed Implementation
[0028] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0029] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0030] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0031] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.
[0032] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0033] This invention provides a method for preparing an easily recyclable three-dimensional nanoporous foam catalyst Fe2O3@N-rGF, comprising the following steps: Fe(NO3)3·9H2O and urea (urea serves as a nitrogen source, pore-forming agent, and homogeneous precipitant) are mixed evenly to obtain an iron precursor solution, which is then mixed with GO dispersion to obtain a mixed solution. The mixture is transferred to a hydrothermal reactor for a one-step hydrothermal reaction. After the reaction was completed, the product was washed and dried to obtain the easily recyclable three-dimensional nanoporous foam catalyst Fe2O3@N-rGF.
[0034] In a preferred embodiment of the present invention, the concentration of the GO dispersion is 2 g / L. The GO dispersion is prepared from natural flake graphite using a modified Hummers process, specifically including the following steps: 2.5 g of natural flake graphite (1000 mesh) was added to a beaker containing 60 mL of concentrated H2SO4, 7.5 g of KMnO4 and 1.25 g of NaNO3. The mixture was stirred at 5 °C for 2 h. Then, the system was heated to 35 °C and kept at that temperature for 1 h. 120 mL of deionized water cooled in an ice-water bath was then slowly added. The mixture was then transferred to a reaction vessel and kept at 93 °C for 30 min. After the reaction solution cooled to room temperature, it was diluted to 350 mL with 35 °C deionized water. 100 mL of 6% H2O2 solution was then added. After the reaction was complete, a yellow turbid liquid was obtained. The product was centrifuged and washed successively with 1 mol / L hydrochloric acid solution and deionized water until neutral. After drying, GO was obtained. Finally, GO was ultrasonically dispersed in deionized water for 3 h to obtain a GO dispersion with a concentration of 2 g / L.
[0035] In a preferred embodiment of the present invention, the concentration of Fe(NO3)3·9H2O in the iron precursor solution is 0.2 M to 0.5 M; preferably 0.3 M.
[0036] In a preferred embodiment of the present invention, the volume ratio of GO dispersion to iron precursor solution is (4.5~11.5):0.5; preferably 6.5:0.5.
[0037] In a preferred embodiment of the present invention, the reaction temperature of the one-step hydrothermal reaction is 120~210 ℃ and the reaction time is 12~24 h; preferably, the reaction temperature is 180 ℃ and the reaction time is 12 h.
[0038] In a preferred embodiment of the present invention, washing is performed with deionized water until neutral, and drying is performed by natural air drying.
[0039] This invention also provides a three-dimensional nanoporous foam catalyst Fe2O3@N-rGF prepared according to the above preparation method.
[0040] The catalyst prepared in this invention is a bulk three-dimensional nanoporous foam material, with N-rGF forming a three-dimensional interconnected porous network framework, possessing a high specific surface area and a well-developed mesoporous structure. Fe2O3 nanoparticles are uniformly anchored on the surface and inner walls of the pores of N-rGF via homogeneous precipitation, achieving high dispersion and stable loading of the active components. The nitrogen doping forms in the N-rGF include pyridine nitrogen, pyrrole nitrogen, graphitic nitrogen, and nitrogen oxides (NOx). X ) species. Among them, nitrogen species containing lone pairs of electrons, such as pyridine nitrogen and pyrrole nitrogen, can form strong coordination with Fe2O3 nanoparticles, thereby significantly enhancing the anchoring stability of the active components on the carbon framework and effectively inhibiting the leaching of metal ions.
[0041] This invention also provides an application of the above-mentioned three-dimensional nanoporous foam catalyst Fe2O3@N-rGF in the degradation of organic pollutants in water by activated PDS, wherein the organic pollutants include at least one of BPA, BPF and BPS.
[0042] In a preferred embodiment of the present invention, the concentration of organic pollutants in the water is 0.5~14 mg / L, and the concentration of PDS in the water is 0.3~1.8 mM.
[0043] In a preferred embodiment of the present invention, the degradation is carried out in water with a pH of 3.0 to 11.0.
[0044] In a preferred embodiment of the present invention, the water body is deionized water, tap water, river water, or effluent from a sewage treatment plant.
[0045] In a preferred embodiment of the present invention, after the catalyst activates PDS to degrade organic pollutants, it can be recovered and reused through simple separation.
[0046] Taking BPA as an example, the specific steps of using the three-dimensional nanoporous foam catalyst Fe2O3@N-rGF to activate PDS for the degradation of BPA in water are as follows: First, the three-dimensional nanoporous foam catalyst Fe2O3@N-rGF was placed in a clamp, which was then connected to the inlet of a peristaltic pump. The clamp, along with the pump outlet, was then placed into a beaker containing 50 mL of BPA solution, forming a closed-loop circuit. The peristaltic pump was run at a flow rate of 3 mL / min for 2 h to allow the catalyst to reach adsorption equilibrium. Then, PDS was added to the beaker, and the reaction continued for 90 min. Samples were taken at predetermined time intervals. All samples were filtered through a 0.45 µm glass fiber membrane and stored at 4 °C for analysis (the above experiments were repeated three times, and the relative error of the experimental data was ≤5%).
[0047] The technical solution of the present invention will be further described below through embodiments.
[0048] Example 1 (1) 2.5 g of natural flake graphite (1000 mesh) was added to a beaker containing 60 mL of concentrated H2SO4, 7.5 g of KMnO4 and 1.25 g of NaNO3, and stirred at 5 °C for 2 h. Then, the system was heated to 35 °C and kept at that temperature for 1 h, and then slowly poured into 120 mL of deionized water cooled in an ice-water bath. The mixture was then transferred to a reaction vessel and kept at 93 °C for 30 min. After the reaction solution cooled to room temperature, it was diluted to 350 mL with 35 °C deionized water, and then 100 mL of 6% H2O2 solution was added. After the reaction was complete, a yellow turbid liquid was obtained. The mixture was centrifuged and washed with 1 mol / L hydrochloric acid and deionized water until neutral. After drying, GO was obtained. Finally, GO was ultrasonically dispersed in deionized water for 3 h to obtain a GO dispersion with a concentration of 2 g / L.
[0049] (2) Dissolve 0.8 g Fe(NO3)3·9H2O and 0.45 g urea in 10 mL of deionized water and stir for 30 min to obtain a 0.2 M Fe precursor solution. Take 0.5 mL of the above precursor solution and add it to 6.5 mL of the GO dispersion prepared in step (1), and stir for 5 min to mix thoroughly. Transfer the mixture to a hydrothermal reactor and react at 180 °C for 12 h. After the reaction is complete, take out the product, wash it with deionized water until neutral, and air dry it at room temperature to obtain the blocky three-dimensional nanoporous foam Fe2O3@N-rGF catalyst prepared from the 0.2 M Fe precursor solution.
[0050] (3) Take one Fe2O3@N-rGF catalyst (0.018 g) and place it in a clamp. Connect the clamp to the inlet of the peristaltic pump, and then place the clamp and the pump outlet together into a beaker containing 50 mL of BPA solution (prepared with deionized water) with a concentration of 5 mg / L to form a closed loop. Circulate at a flow rate of 3 mL / min for 2 h to allow the catalyst to reach adsorption equilibrium. Then add PDS to the beaker to a concentration of 0.6 mM and continue the reaction for 90 min. After the reaction is completed, measure the BPA removal rate. The results are shown in […]. Figure 1 The removal rate was 96.85%.
[0051] Example 2 (1) A GO dispersion was prepared according to the method of step (1) in Example 1 to obtain a GO dispersion with a concentration of 2 g / L.
[0052] (2) Dissolve 1.2 g Fe(NO3)3·9H2O and 0.45 g urea in 10 mL of deionized water and stir for 30 min to obtain a 0.3 M Fe precursor solution. Take 0.5 mL of the above precursor solution and add it to 6.5 mL of the GO dispersion obtained in step (1), and stir for 5 min to mix thoroughly. Transfer the mixture to a hydrothermal reactor and react at 180 °C for 12 h. After the reaction is complete, take out the product, wash it with deionized water until neutral, and air dry it at room temperature to obtain the blocky three-dimensional nanoporous foam Fe2O3@N-rGF catalyst prepared from the 0.3 M Fe precursor solution.
[0053] (3) Following the test method in step (3) of Example 1, one Fe2O3@N-rGF catalyst (0.018 g) prepared in step (2) was taken and tested for its ability to degrade BPA by activating PDS under the same conditions as in Example 1 (BPA solution concentration 5 mg / L, volume 50 mL, PDS concentration 0.6 mM, flow rate 3 mL / min). The results are shown in […]. Figure 1 The BPA removal rate is 100%.
[0054] Example 3 (1) A GO dispersion was prepared according to the method of step (1) in Example 1 to obtain a GO dispersion with a concentration of 2 g / L.
[0055] (2) Dissolve 1.6 g Fe(NO3)3·9H2O and 0.45 g urea in 10 mL of deionized water and stir for 30 min to obtain a 0.4 M Fe precursor solution. Take 0.5 mL of the above precursor solution and add it to 6.5 mL of the GO dispersion obtained in step (1), and stir for 5 min to mix thoroughly. Transfer the mixture to a hydrothermal reactor and react at 180 °C for 12 h. After the reaction is complete, take out the product, wash it with deionized water until neutral, and air dry it at room temperature to obtain the blocky three-dimensional nanoporous foam Fe2O3@N-rGF catalyst prepared from the 0.4 M Fe precursor solution.
[0056] (3) Following the test method in step (3) of Example 1, one Fe2O3@N-rGF catalyst (0.018 g) prepared in step (2) was taken and tested for its ability to degrade BPA by activating PDS under the same conditions as in Example 1 (BPA solution concentration 5 mg / L, volume 50 mL, PDS concentration 0.6 mM, flow rate 3 mL / min). The results are shown in […]. Figure 1 The BPA removal rate was 97.47%.
[0057] Example 4 (1) A GO dispersion was prepared according to the method of step (1) in Example 1 to obtain a GO dispersion with a concentration of 2 g / L.
[0058] (2) Dissolve 2.0 g Fe(NO3)3·9H2O and 0.45 g urea in 10 mL of deionized water and stir for 30 min to obtain a 0.5 M Fe precursor solution. Take 0.5 mL of the above precursor solution and add it to 6.5 mL of the GO dispersion obtained in step (1), and stir for 5 min to mix thoroughly. Transfer the mixture to a hydrothermal reactor and react at 180 °C for 12 h. After the reaction is complete, take out the product, wash it with deionized water until neutral, and air dry it at room temperature to obtain the blocky three-dimensional nanoporous foam Fe2O3@N-rGF catalyst prepared from the 0.5 M Fe precursor solution.
[0059] (3) Following the test method in step (3) of Example 1, one Fe2O3@N-rGF catalyst (0.018 g) prepared in step (2) was taken and tested for its ability to degrade BPA by activating PDS under the same conditions as in Example 1 (BPA solution concentration 5 mg / L, volume 50 mL, PDS concentration 0.6 mM, flow rate 3 mL / min). The results are shown in […]. Figure 1 The BPA removal rate was 94.82%.
[0060] Example 5 (1) A GO dispersion was prepared according to the method of step (1) in Example 1 to obtain a GO dispersion with a concentration of 2 g / L.
[0061] (2) Dissolve 1.2 g Fe(NO3)3·9H2O and 0.45 g urea in 10 mL of deionized water and stir for 30 min to obtain a Fe precursor solution with a concentration of 0.3 M. Take 0.5 mL of the above Fe precursor solution and add it to 4.5 mL of the GO dispersion obtained in step (1), and stir for 5 min to mix thoroughly. Transfer the mixture to a hydrothermal reactor and react at 180 °C for 12 h. After the reaction is complete, take out the product, wash it with deionized water until neutral, and air dry it naturally at room temperature to obtain the blocky three-dimensional nanoporous foam Fe2O3@N-rGF catalyst prepared from 4.5 mL of GO dispersion.
[0062] (3) Following the test method in step (3) of Example 1, one Fe2O3@N-rGF catalyst (0.018 g) prepared in step (2) was taken and tested for its ability to degrade BPA by activating PDS under the same conditions as in Example 1 (BPA solution concentration 5 mg / L, volume 50 mL, PDS concentration 0.6 mM, flow rate 3 mL / min). The results are shown in […]. Figure 2 The BPA removal rate was 30.02%.
[0063] Example 6 (1) A GO dispersion was prepared according to the method of step (1) in Example 1 to obtain a GO dispersion with a concentration of 2 g / L.
[0064] (2) Dissolve 1.2 g Fe(NO3)3·9H2O and 0.45 g urea in 10 mL of deionized water and stir for 30 min to obtain a Fe precursor solution with a concentration of 0.3 M. Take 0.5 mL of the above Fe precursor solution and add it to 6.5 mL of the GO dispersion obtained in step (1), and stir for 5 min to mix thoroughly. Transfer the mixture to a hydrothermal reactor and react at 180 °C for 12 h. After the reaction is complete, take out the product, wash it with deionized water until neutral, and air dry it naturally at room temperature to obtain the blocky three-dimensional nanoporous foam Fe2O3@N-rGF catalyst prepared from 6.5 mL of GO dispersion.
[0065] (3) Following the test method in step (3) of Example 1, one Fe2O3@N-rGF catalyst (0.018 g) prepared in step (2) was taken and tested for its ability to degrade BPA by activating PDS under the same conditions as in Example 1 (BPA solution concentration 5 mg / L, volume 50 mL, PDS concentration 0.6 mM, flow rate 3 mL / min). The results are shown in […]. Figure 2 The BPA removal rate was 94.39%.
[0066] Example 7 (1) A GO dispersion was prepared according to the method of step (1) in Example 1 to obtain a GO dispersion with a concentration of 2 g / L.
[0067] (2) Dissolve 1.2 g Fe(NO3)3·9H2O and 0.45 g urea in 10 mL of deionized water and stir for 30 min to obtain a Fe precursor solution with a concentration of 0.3 M. Take 0.5 mL of the above Fe precursor solution and add it to 9.5 mL of the GO dispersion obtained in step (1), and stir for 5 min to mix thoroughly. Transfer the mixture to a hydrothermal reactor and react at 180 °C for 12 h. After the reaction is complete, take out the product, wash it with deionized water until neutral, and air dry it naturally at room temperature to obtain the blocky three-dimensional nanoporous foam Fe2O3@N-rGF catalyst prepared from 9.5 mL of GO dispersion.
[0068] (3) Following the test method in step (3) of Example 1, one Fe2O3@N-rGF catalyst (0.018 g) prepared in step (2) was taken and tested for its ability to degrade BPA by activating PDS under the same conditions as in Example 1 (BPA solution concentration 5 mg / L, volume 50 mL, PDS concentration 0.6 mM, flow rate 3 mL / min). The results are shown in […]. Figure 2 The BPA removal rate was 98.99%.
[0069] Example 8 (1) A GO dispersion was prepared according to the method of step (1) in Example 1 to obtain a GO dispersion with a concentration of 2 g / L.
[0070] (2) Dissolve 1.2 g Fe(NO3)3·9H2O and 0.45 g urea in 10 mL of deionized water and stir for 30 min to obtain a Fe precursor solution with a concentration of 0.3 M. Take 0.5 mL of the above Fe precursor solution and add it to 11.5 mL of the GO dispersion obtained in step (1) and stir for 5 min to mix thoroughly. Transfer the mixture to a hydrothermal reactor and react at 180 °C for 12 h. After the reaction is complete, take out the product, wash it with deionized water until neutral, and air dry it naturally at room temperature to obtain the blocky three-dimensional nanoporous foam Fe2O3@N-rGF catalyst prepared from 11.5 mL of GO dispersion.
[0071] (3) Following the test method in step (3) of Example 1, one Fe2O3@N-rGF catalyst (0.018 g) prepared in step (2) was taken and tested for its ability to degrade BPA by activating PDS under the same conditions as in Example 1 (BPA solution concentration 5 mg / L, volume 50 mL, PDS concentration 0.6 mM, flow rate 3 mL / min). The results are shown in […]. Figure 2 The BPA removal rate was 94.45%.
[0072] Example 9 (1) A GO dispersion was prepared according to the method of step (1) in Example 1 to obtain a GO dispersion with a concentration of 2 g / L.
[0073] (2) Dissolve 1.2 g Fe(NO3)3·9H2O and 0.45 g urea in 10 mL of deionized water and stir for 30 min to obtain a Fe precursor solution with a concentration of 0.3 M. Take 0.5 mL of the above Fe precursor solution and add it to 6.5 mL of the GO dispersion obtained in step (1), and stir for 5 min to mix thoroughly. Transfer the mixture to a hydrothermal reactor and react at 120 °C for 12 h. After the reaction is complete, take out the product, wash it with deionized water until neutral, and air dry it naturally at room temperature to obtain the blocky three-dimensional nanoporous foam Fe2O3@N-rGF catalyst prepared under hydrothermal conditions at 120 °C.
[0074] (3) Following the test method in step (3) of Example 1, one Fe2O3@N-rGF catalyst (0.018 g) prepared in step (2) was taken and tested for its ability to degrade BPA by activating PDS under the same conditions as in Example 1 (BPA solution concentration 5 mg / L, volume 50 mL, PDS concentration 0.6 mM, flow rate 3 mL / min). The results are shown in […]. Figure 3 (The illustration is a picture of the actual product), the BPA removal rate is 92.64%.
[0075] Example 10 (1) A GO dispersion was prepared according to the method of step (1) in Example 1 to obtain a GO dispersion with a concentration of 2 g / L.
[0076] (2) Dissolve 1.2 g Fe(NO3)3·9H2O and 0.45 g urea in 10 mL of deionized water and stir for 30 min to obtain a Fe precursor solution with a concentration of 0.3 M. Take 0.5 mL of the above Fe precursor solution and add it to 6.5 mL of the GO dispersion obtained in step (1), and stir for 5 min to mix thoroughly. Transfer the mixture to a hydrothermal reactor and react at 150 °C for 12 h. After the reaction is complete, take out the product, wash it with deionized water until neutral, and air dry it naturally at room temperature to obtain the blocky three-dimensional nanoporous foam Fe2O3@N-rGF catalyst prepared under hydrothermal conditions at 150 °C.
[0077] (3) Following the test method in step (3) of Example 1, one Fe2O3@N-rGF catalyst (0.018 g) prepared in step (2) was taken and tested for its ability to degrade BPA by activating PDS under the same conditions as in Example 1 (BPA solution concentration 5 mg / L, volume 50 mL, PDS concentration 0.6 mM, flow rate 3 mL / min). The results are shown in […]. Figure 3 (The illustration is a picture of the actual product), the BPA removal rate is 86.42%.
[0078] Example 11 (1) A GO dispersion was prepared according to the method of step (1) in Example 1 to obtain a GO dispersion with a concentration of 2 g / L.
[0079] (2) Dissolve 1.2 g Fe(NO3)3·9H2O and 0.45 g urea in 10 mL of deionized water and stir for 30 min to obtain a Fe precursor solution with a concentration of 0.3 M. Take 0.5 mL of the above Fe precursor solution and add it to 6.5 mL of the GO dispersion obtained in step (1), and stir for 5 min to mix thoroughly. Transfer the mixture to a hydrothermal reactor and react at 180 °C for 12 h. After the reaction is complete, take out the product, wash it with deionized water until neutral, and air dry it naturally at room temperature to obtain the blocky three-dimensional nanoporous foam catalyst Fe2O3@N-rGF prepared under hydrothermal conditions at 180 °C.
[0080] (3) Following the test method in step (3) of Example 1, one Fe2O3@N-rGF catalyst (0.018 g) prepared in step (2) was taken and tested for its ability to degrade BPA by activating PDS under the same conditions as in Example 1 (BPA solution concentration 5 mg / L, volume 50 mL, PDS concentration 0.6 mM, flow rate 3 mL / min). The results are shown in […]. Figure 3 (The illustration is a picture of the actual product), the BPA removal rate is 91.09%.
[0081] Example 12 (1) A GO dispersion was prepared according to the method of step (1) in Example 1 to obtain a GO dispersion with a concentration of 2 g / L.
[0082] (2) Dissolve 1.2 g Fe(NO3)3·9H2O and 0.45 g urea in 10 mL of deionized water and stir for 30 min to obtain a Fe precursor solution with a concentration of 0.3 M. Take 0.5 mL of the above Fe precursor solution and add it to 6.5 mL of the GO dispersion obtained in step (1), and stir for 5 min to mix thoroughly. Transfer the mixture to a hydrothermal reactor and react at 210 °C for 12 h. After the reaction is complete, take out the product, wash it with deionized water until neutral, and air dry it naturally at room temperature to obtain the blocky three-dimensional nanoporous foam catalyst Fe2O3@N-rGF prepared under hydrothermal conditions at 210 °C.
[0083] (3) Following the test method in step (3) of Example 1, one Fe2O3@N-rGF catalyst (0.018 g) prepared in step (2) was taken and tested for its ability to degrade BPA by activating PDS under the same conditions as in Example 1 (BPA solution concentration 5 mg / L, volume 50 mL, PDS concentration 0.6 mM, flow rate 3 mL / min). The results are shown in […]. Figure 3(The illustration is a picture of the actual product), the BPA removal rate is 84.90%.
[0084] Example 13 (1) A GO dispersion was prepared according to the method of step (1) in Example 1 to obtain a GO dispersion with a concentration of 2 g / L.
[0085] (2) Dissolve 1.2 g Fe(NO3)3·9H2O and 0.45 g urea in 10 mL of deionized water and stir for 30 min to obtain a Fe precursor solution with a concentration of 0.3 M. Take 0.5 mL of the above Fe precursor solution and add it to 6.5 mL of the GO dispersion obtained in step (1), and stir for 5 min to mix thoroughly. Transfer the mixture to a hydrothermal reactor and react at 180 °C for 12 h. After the reaction is completed, take out the product, wash it with deionized water until neutral, and air dry it at room temperature to obtain the blocky three-dimensional nanoporous foam Fe2O3@N-rGF catalyst prepared under hydrothermal reaction time of 12 h.
[0086] (3) Following the test method in step (3) of Example 1, one Fe2O3@N-rGF catalyst (0.018 g) prepared in step (2) was taken and tested for its ability to degrade BPA by activating PDS under the same conditions as in Example 1 (BPA solution concentration 5 mg / L, volume 50 mL, PDS concentration 0.6 mM, flow rate 3 mL / min). The results are shown in […]. Figure 4 (The illustration is a picture of the actual product), the BPA removal rate is 94.01%.
[0087] Example 14 (1) A GO dispersion was prepared according to the method of step (1) in Example 1 to obtain a GO dispersion with a concentration of 2 g / L.
[0088] (2) Dissolve 1.2 g Fe(NO3)3·9H2O and 0.45 g urea in 10 mL of deionized water and stir for 30 min to obtain a Fe precursor solution with a concentration of 0.3 M. Take 0.5 mL of the above Fe precursor solution and add it to 6.5 mL of the GO dispersion obtained in step (1), and stir for 5 min to mix thoroughly. Transfer the mixture to a hydrothermal reactor and react at 180 °C for 16 h. After the reaction is complete, take out the product, wash it with deionized water until neutral, and air dry it naturally at room temperature to obtain the blocky three-dimensional nanoporous foam Fe2O3@N-rGF catalyst prepared under hydrothermal reaction time of 16 h.
[0089] (3) Following the test method in step (3) of Example 1, one Fe2O3@N-rGF catalyst (0.018 g) prepared in step (2) was taken and tested for its ability to degrade BPA by activating PDS under the same conditions as in Example 1 (BPA solution concentration 5 mg / L, volume 50 mL, PDS concentration 0.6 mM, flow rate 3 mL / min). The results are shown in […]. Figure 4 (The illustration is a picture of the actual product), the BPA removal rate is 87.49%.
[0090] Example 15 (1) A GO dispersion was prepared according to the method of step (1) in Example 1 to obtain a GO dispersion with a concentration of 2 g / L.
[0091] (2) Dissolve 1.2 g Fe(NO3)3·9H2O and 0.45 g urea in 10 mL of deionized water and stir for 30 min to obtain a Fe precursor solution with a concentration of 0.3 M. Take 0.5 mL of the above Fe precursor solution and add it to 6.5 mL of the GO dispersion obtained in step (1), and stir for 5 min to mix thoroughly. Transfer the mixture to a hydrothermal reactor and react at 180 °C for 20 h. After the reaction is complete, take out the product, wash it with deionized water until neutral, and air dry it naturally at room temperature to obtain the blocky three-dimensional nanoporous foam Fe2O3@N-rGF catalyst prepared under hydrothermal reaction conditions of 20 h.
[0092] (3) Following the test method in step (3) of Example 1, one Fe2O3@N-rGF catalyst (0.018 g) prepared in step (2) was taken and tested for its ability to degrade BPA by activating PDS under the same conditions as in Example 1 (BPA solution concentration 5 mg / L, volume 50 mL, PDS concentration 0.6 mM, flow rate 3 mL / min). The results are shown in […]. Figure 4 (The illustration is a picture of the actual product), the BPA removal rate is 91.85%.
[0093] Example 16 (1) A GO dispersion was prepared according to the method of step (1) in Example 1 to obtain a GO dispersion with a concentration of 2 g / L.
[0094] (2) Dissolve 1.2 g Fe(NO3)3·9H2O and 0.45 g urea in 10 mL of deionized water and stir for 30 min to obtain a Fe precursor solution with a concentration of 0.3 M. Take 0.5 mL of the above Fe precursor solution and add it to 6.5 mL of the GO dispersion obtained in step (1), and stir for 5 min to mix thoroughly. Transfer the mixture to a hydrothermal reactor and react at 180 °C for 24 h. After the reaction is completed, take out the product, wash it with deionized water until neutral, and air dry it naturally at room temperature to obtain the blocky three-dimensional nanoporous foam Fe2O3@N-rGF catalyst prepared under hydrothermal reaction time of 24 h.
[0095] (3) Following the test method in step (3) of Example 1, one Fe2O3@N-rGF catalyst (0.018 g) prepared in step (2) was taken and tested for its ability to degrade BPA by activating PDS under the same conditions as in Example 1 (BPA solution concentration 5 mg / L, volume 50 mL, PDS concentration 0.6 mM, flow rate 3 mL / min). The results are shown in […]. Figure 4 (The illustration is a picture of the actual product), the BPA removal rate is 85.58%.
[0096] Too low a hydrothermal reaction temperature (120℃) will lead to incomplete GO reduction and self-assembly, resulting in a loose catalyst structure (see...). Figure 3 (See illustration in the middle); Excessively high hydrothermal reaction temperatures (210℃) result in uneven catalyst structure and insufficient mechanical strength, making it difficult to maintain a stable blocky morphology (see illustration in the middle). Figure 3 (See illustration in the middle). Based on the results of Examples 1-16, and considering both catalytic performance and economic cost, the optimal preparation conditions for the three-dimensional nanoporous foam catalyst Fe2O3@N-rGF were determined to be: hydrothermal reaction temperature 180℃, reaction time 12 h, Fe precursor solution concentration 0.3 M, and GO dispersion volume 6.5 mL. Subsequent examples all used the above optimal conditions for catalyst preparation.
[0097] The physical image (a), scanning electron microscope (SEM) images (b, c, with the inset in c showing the particle size distribution of Fe2O3 in Fe2O3@N-rGF) of the bulk three-dimensional nanoporous foam catalyst Fe2O3@N-rGF prepared under optimal conditions, energy dispersive spectroscopy (d), and transmission electron microscope (TEM) images (e, f) at different resolutions are shown below. Figure 5As shown in the figure, the prepared catalyst is a black, blocky, three-dimensional nanoporous foam material. It uses N-rGF to form a three-dimensional interconnected porous network framework, possessing both high specific surface area and a well-developed mesoporous structure. Fe2O3 nanoparticles are uniformly anchored on the surface and inner walls of the pores of N-rGF through in-situ growth, achieving high dispersion and stable loading of the active components. Comparative experiments were conducted to verify the key roles of GO and urea in the preparation process of this invention.
[0098] Comparative Example 1 Under optimal conditions (Example 28), the addition of GO is omitted, specifically: 0.8 g of Fe(NO3)3·9H2O and 0.45 g of urea were dissolved in 10 mL of deionized water and stirred for 30 min to prepare a 0.3 M Fe precursor solution. 0.5 mL of the above precursor solution was transferred to a hydrothermal reactor and reacted at 180 °C for 12 h. After the reaction was complete, the product was removed, washed with deionized water until neutral, and air-dried at room temperature to obtain the final product.
[0099] Comparative Example 2 Under optimal conditions (Example 28), NaOH is used instead of urea as the precipitant, specifically: 0.8 g of Fe(NO3)3·9H2O and 0.45 g of NaOH were dissolved in 10 mL of deionized water and stirred for 30 min to obtain a 0.3 M Fe precursor solution. 0.5 mL of the above precursor solution was added to 6.5 mL of GO dispersion (prepared as in Example 1) and stirred for 5 min to ensure thorough mixing. The mixture was transferred to a hydrothermal reactor and reacted at 180 °C for 12 h. After the reaction was complete, the product was removed, washed with deionized water until neutral, and air-dried at room temperature to obtain the final product.
[0100] Figure 6 The images show scanning electron microscope (SEM) images at different magnifications of the materials obtained in Comparative Example 1 (without GO), Comparative Example 2 (with NaOH instead of urea as the precipitant) (b), and the material prepared under the optimal conditions of this invention (c). The inset shows the particle size distribution of Fe2O3 in each material. It can be seen that without GO, the Fe2O3 particles exhibit significant agglomeration; when NaOH is used instead of urea as the precipitant, the Fe2O3 particles exhibit a large-sized strip-like structure.
[0101] Example 17 (1) A GO dispersion was prepared according to the method of step (1) in Example 1 to obtain a GO dispersion with a concentration of 2 g / L.
[0102] (2) According to the optimal preparation conditions (hydrothermal reaction temperature 180℃, reaction time 12 h, Fe precursor solution concentration 0.3 M, GO dispersion volume 6.5 mL), the same method as step (2) of Example 1 was used to prepare the blocky three-dimensional nanoporous foam catalyst Fe2O3@N-rGF.
[0103] (3) Take one Fe2O3@N-rGF catalyst (0.018 g) obtained in step (2) and test its recyclability for BPA degradation using activated PDS. The test conditions were: initial BPA solution concentration of 2 mg / L (prepared with deionized water), volume of 50 mL, and PDS concentration of 0.6 mM. After each reaction, the catalyst was not treated in any way. Instead, a beaker containing 50 mL of fresh BPA solution (2 mg / L, prepared with deionized water) was directly replaced, and the degradation experiment was repeated according to the same procedure for a total of 5 cycles. The results are shown in […]. Figure 7 The BPA removal rates for the first to fifth cycles were 91.76%, 96.25%, 92.53%, 86.85%, and 90.59%, respectively.
[0104] Example 18 (1) A GO dispersion was prepared according to the method of step (1) in Example 1 to obtain a GO dispersion with a concentration of 2 g / L.
[0105] (2) According to the optimal preparation conditions (hydrothermal reaction temperature 180℃, reaction time 12 h, Fe precursor solution concentration 0.3 M, GO dispersion volume 6.5 mL), the same method as step (2) of Example 1 was used to prepare the blocky three-dimensional nanoporous foam Fe2O3@N-rGF catalyst.
[0106] (3) Take one Fe2O3@N-rGF catalyst (0.018 g) prepared in step (2), adjust the pH of the solution to 3.00 with 0.1 mM hydrochloric acid, and the remaining test conditions are the same as in step (3) of Example 1 (BPA solution concentration 5 mg / L, volume 50 mL, PDS concentration 0.6 mM, flow rate 3 mL / min), test its performance in activating PDS to degrade BPA, and at the same time determine the corresponding iron ion leaching amount. The results are shown in Figure 8 Where a represents the performance in degrading BPA and b represents the amount of iron ions leached out, it can be seen that the BPA removal rate is 90.50% and the amount of iron ions leached out is 0.0728 mg / L.
[0107] Example 19 (1) A GO dispersion was prepared according to the method of step (1) in Example 1 to obtain a GO dispersion with a concentration of 2 g / L.
[0108] (2) According to the optimal preparation conditions (hydrothermal reaction temperature 180℃, reaction time 12 h, Fe precursor solution concentration 0.3 M, GO dispersion volume 6.5 mL), the same method as step (2) of Example 1 was used to prepare the blocky three-dimensional nanoporous foam Fe2O3@N-rGF catalyst.
[0109] (3) Take one Fe2O3@N-rGF catalyst (0.018 g) prepared in step (2), adjust the pH of the solution to 5.00 with 0.1 mM hydrochloric acid, and the remaining test conditions are the same as in step (3) of Example 1 (BPA solution concentration 5 mg / L, volume 50 mL, PDS concentration 0.6 mM, flow rate 3 mL / min), test its performance in activating PDS to degrade BPA, and at the same time determine the corresponding iron ion leaching amount. The results are shown in Figure 8 Where a represents the performance in degrading BPA and b represents the amount of iron ions leached out, it can be seen that the BPA removal rate is 93.63% and the amount of iron ions leached out is 0.0506 mg / L.
[0110] Example 20 (1) A GO dispersion was prepared according to the method of step (1) in Example 1 to obtain a GO dispersion with a concentration of 2 g / L.
[0111] (2) According to the optimal preparation conditions (hydrothermal reaction temperature 180℃, reaction time 12 h, Fe precursor solution concentration 0.3 M, GO dispersion volume 6.5 mL), the same method as step (2) of Example 1 was used to prepare the blocky three-dimensional nanoporous foam Fe2O3@N-rGF catalyst.
[0112] (3) Take one Fe2O3@N-rGF catalyst (0.018 g) prepared in step (2) and test its performance in activating PDS to degrade BPA under the following conditions: pH 6.70 (without adjustment) and other test conditions as in step (3) of Example 1 (BPA solution concentration 5 mg / L, volume 50 mL, PDS concentration 0.6 mM, flow rate 3 mL / min). Simultaneously, determine the corresponding iron ion leaching amount. See the results below. Figure 8 Where a represents the performance in degrading BPA and b represents the amount of iron ions leached out, it can be seen that the BPA removal rate is 94.53% and the amount of iron ions leached out is 0.0398 mg / L.
[0113] Example 21 (1) A GO dispersion was prepared according to the method of step (1) in Example 1 to obtain a GO dispersion with a concentration of 2 g / L.
[0114] (2) According to the optimal preparation conditions (hydrothermal reaction temperature 180℃, reaction time 12 h, Fe precursor solution concentration 0.3 M, GO dispersion volume 6.5 mL), the same method as step (2) of Example 1 was used to prepare the blocky three-dimensional nanoporous foam Fe2O3@N-rGF catalyst.
[0115] (3) Take one Fe2O3@N-rGF catalyst (0.018 g) prepared in step (2), adjust the pH to 9.00 with 1 mM NaOH solution, and the remaining test conditions are the same as in step (3) of Example 1 (BPA solution concentration 5 mg / L, volume 50 mL, PDS concentration 0.6 mM, flow rate 3 mL / min). Test its performance in activating PDS to degrade BPA, and at the same time determine the corresponding iron ion leaching amount. The results are shown in […]. Figure 8 The BPA removal rate was 94.87%, and the iron ion leaching amount was 0.0484 mg / L.
[0116] Example 22 (1) A GO dispersion was prepared according to the method of step (1) in Example 1 to obtain a GO dispersion with a concentration of 2 g / L.
[0117] (2) According to the optimal preparation conditions (hydrothermal reaction temperature 180℃, reaction time 12 h, Fe precursor solution concentration 0.3 M, GO dispersion volume 6.5 mL), the same method as step (2) of Example 1 was used to prepare the blocky three-dimensional nanoporous foam Fe2O3@N-rGF catalyst.
[0118] (3) Take one Fe2O3@N-rGF catalyst (0.018 g) prepared in step (2), adjust the pH to 11.00 with 1 mM NaOH solution, and keep the other test conditions the same as in step (3) of Example 1 (BPA solution concentration 5 mg / L, volume 50 mL, PDS concentration 0.6 mM, flow rate 3 mL / min), test its performance in activating PDS to degrade BPA, and simultaneously determine the corresponding iron ion leaching amount. The results are shown in […]. Figure 8 The BPA removal rate was 92.78%, and the iron ion leaching amount was 0.0507 mg / L.
[0119] Example 23 (1) A GO dispersion was prepared according to the method of step (1) in Example 1 to obtain a GO dispersion with a concentration of 2 g / L.
[0120] (2) According to the optimal preparation conditions (hydrothermal reaction temperature 180℃, reaction time 12 h, Fe precursor solution concentration 0.3 M, GO dispersion volume 6.5 mL), the same method as step (2) of Example 1 was used to prepare the blocky three-dimensional nanoporous foam catalyst Fe2O3@N-rGF.
[0121] (3) Take one Fe2O3@N-rGF catalyst (0.018 g) obtained in step (2) and prepare a BPA solution with a concentration of 5 mg / L using tap water as the preparation medium. The remaining test conditions are the same as in step (3) of Example 1 (volume 50 mL, PDS concentration 0.6 mM, flow rate 3 mL / min). Test its performance in activating PDS to degrade BPA. The results are shown in […]. Figure 9 The BPA removal rate was 96.53%.
[0122] Example 24 (1) A GO dispersion was prepared according to the method of step (1) in Example 1 to obtain a GO dispersion with a concentration of 2 g / L.
[0123] (2) According to the optimal preparation conditions (hydrothermal reaction temperature 180℃, reaction time 12 h, Fe precursor solution concentration 0.3 M, GO dispersion volume 6.5 mL), the same method as step (2) of Example 1 was used to prepare the blocky three-dimensional nanoporous foam catalyst Fe2O3@N-rGF.
[0124] (3) Take one Fe2O3@N-rGF catalyst (0.018 g) obtained in step (2) and prepare a BPA solution with a concentration of 5 mg / L using river water as the preparation medium. The remaining test conditions are the same as in step (3) of Example 1 (volume 50 mL, PDS concentration 0.6 mM, flow rate 3 mL / min). Test its performance in activating PDS to degrade BPA. The results are shown in […]. Figure 9 The BPA removal rate was 97.48%.
[0125] Example 25 (1) A GO dispersion was prepared according to the method of step (1) in Example 1 to obtain a GO dispersion with a concentration of 2 g / L.
[0126] (2) According to the optimal preparation conditions (hydrothermal reaction temperature 180℃, reaction time 12 h, Fe precursor solution concentration 0.3 M, GO dispersion volume 6.5 mL), the same method as step (2) of Example 1 was used to prepare the blocky three-dimensional nanoporous foam catalyst Fe2O3@N-rGF.
[0127] (3) Take one Fe2O3@N-rGF catalyst (0.018 g) obtained in step (2) and prepare a BPA solution with a concentration of 5 mg / L using wastewater effluent as the preparation medium. The remaining test conditions are the same as in step (3) of Example 1 (volume 50 mL, PDS concentration 0.6 mM, flow rate 3 mL / min). Test its performance in activating PDS to degrade BPA. The results are shown in […]. Figure 9 The BPA removal rate was 96.81%.
[0128] Example 26 (1) A GO dispersion was prepared according to the method of step (1) in Example 1 to obtain a GO dispersion with a concentration of 2 g / L.
[0129] (2) According to the optimal preparation conditions (hydrothermal reaction temperature 180℃, reaction time 12 h, Fe precursor solution concentration 0.3 M, GO dispersion volume 6.5 mL), the same method as step (2) of Example 1 was used to prepare the blocky three-dimensional nanoporous foam catalyst Fe2O3@N-rGF.
[0130] (3) Take one Fe2O3@N-rGF catalyst (0.018 g) obtained in step (2) and prepare a bisphenol F (BPF) solution with a concentration of 5 mg / L using deionized water as the preparation medium. The remaining test conditions are the same as in step (3) of Example 1 (volume 50 mL, PDS concentration 0.6 mM, flow rate 3 mL / min). Test its performance in activating PDS to degrade BPF and the corresponding degradation rate constant. The results are shown in […]. Figure 10 The BPF removal rate was 100%, and the degradation rate constant was 0.0418 min. -1 .
[0131] Example 27 (1) A GO dispersion was prepared according to the method of step (1) in Example 1 to obtain a GO dispersion with a concentration of 2 g / L.
[0132] (2) According to the optimal preparation conditions (hydrothermal reaction temperature 180℃, reaction time 12 h, Fe precursor solution concentration 0.3 M, GO dispersion volume 6.5 mL), the same method as step (2) of Example 1 was used to prepare the blocky three-dimensional nanoporous foam catalyst Fe2O3@N-rGF.
[0133] (3) Take one Fe2O3@N-rGF catalyst (0.018 g) obtained in step (2) and prepare a bisphenol S (BPS) solution with a concentration of 5 mg / L using deionized water as the preparation medium. The other test conditions are the same as in step (3) of Example 1 (volume 50 mL, PDS concentration 0.6 mM, flow rate 3 mL / min). Test its performance in activating PDS to degrade BPS and the corresponding degradation rate constant. The results are shown in […]. Figure 10 The BPS removal rate was 93.29%, and the degradation rate constant was 0.0160 min. -1 .
[0134] Comparative Example 3 (1) 1.2 g Fe(NO3)3·9H2O and 0.45 g urea were dissolved in 10 mL of deionized water and stirred for 30 min to prepare a Fe precursor solution. The solution was transferred to a hydrothermal reactor and reacted at 180 °C for 12 h. After the reaction was completed, the product was taken out, washed with deionized water by centrifugation, and dried to obtain Fe2O3, which was used as a control material for Fe2O3@N-rGF.
[0135] (2) Take 1 Fe2O3 granule (0.018 g) obtained in step (1) and test its performance in degrading BPA with activated PDS under the same conditions as in Example 1 (BPA solution concentration 5 mg / L, volume 50 mL, PDS concentration 0.6 mM, flow rate 3 mL / min). The results are shown in […]. Figure 11 The BPA removal rate was 35.24%, and the degradation rate constant was 0.0016 min. -1 .
[0136] Comparative Example 4 (1) 6.5 mL of GO dispersion with a concentration of 2 g / L was transferred to a hydrothermal reactor and reacted at 180 °C for 12 h. After the reaction was completed, the product was taken out, washed with deionized water until neutral, and air-dried at room temperature to obtain reduced graphene oxide foam (rGF), which was used as a control material for Fe2O3@N-rGF.
[0137] (2) One rGF capsule (0.018 g) obtained in step (1) was tested for its ability to degrade BPA using activated PDS under the same conditions as in Example 1 (BPA solution concentration 5 mg / L, volume 50 mL, PDS concentration 0.6 mM, flow rate 3 mL / min). The results are shown in […]. Figure 11 The BPA removal rate was 43.64%, and the degradation rate constant was 0.0015 min. -1 .
[0138] Comparative Example 5 (1) Dissolve 0.45 g of urea in 10 mL of deionized water and stir for 30 min. Take 0.5 mL of this solution and add it to 6.5 mL of GO dispersion with a concentration of 2 g / L, and stir for 5 min to mix thoroughly. Transfer the mixture to a hydrothermal reactor and react at 180 °C for 12 h. After the reaction is complete, take out the product, wash it with deionized water until neutral, and air dry it at room temperature to obtain nitrogen-doped reduced graphene oxide foam (N-rGF), which serves as a control material for Fe2O3@N-rGF.
[0139] (2) Take one N-rGF capsule (0.018 g) obtained in step (1) and test its performance in degrading BPA with activated PDS under the same conditions as in Example 1 (BPA solution concentration 5 mg / L, volume 50 mL, PDS concentration 0.6 mM, flow rate 3 mL / min). The results are shown in […]. Figure 11 The BPA removal rate was 67.56%, and the degradation rate constant was 0.0068 min. -1 .
[0140] Example 28 (1) A GO dispersion was prepared according to the method of step (1) in Example 1 to obtain a GO dispersion with a concentration of 2 g / L.
[0141] (2) According to the optimal preparation conditions (hydrothermal reaction temperature 180℃, reaction time 12 h, Fe precursor solution concentration 0.3 M, GO dispersion volume 6.5 mL), the same method as step (2) of Example 1 was used to prepare the blocky three-dimensional nanoporous foam catalyst Fe2O3@N-rGF.
[0142] (3) One Fe2O3@N-rGF catalyst (0.018 g) prepared in step (2) was tested for its ability to degrade BPA using activated PDS under the same conditions as in Example 1 (BPA solution concentration 5 mg / L, volume 50 mL, PDS concentration 0.6 mM, flow rate 3 mL / min), and the corresponding degradation rate constant was determined. The results are shown in […]. Figure 11 The removal rate of BPA was 96.94%, and the degradation rate constant was 0.0219 min. -1 .
[0143] In summary, this invention provides a method for preparing an easily recyclable three-dimensional nanoporous foam catalyst, Fe2O3@N-rGF, via a one-step hydrothermal process. This method uses Fe(NO3)3·9H2O as the iron source, GO as the carbon precursor, urea as the nitrogen source, a pore-forming agent, and a homogeneous precipitant. Through a one-step hydrothermal process, the construction of a three-dimensional foam structure, nitrogen doping, and in-situ growth and uniform anchoring of nano-sized Fe2O3 particles are simultaneously achieved, resulting in a Fe2O3@N-rGF foam catalyst with N-rGF as the three-dimensional porous framework and uniformly loaded nano-Fe2O3 particles on the surface and within the pores. In the application of activated PDS for BPA degradation, this catalyst, at a dosage of 0.018 g and a PDS concentration of 0.6 mM, achieved a total removal rate of 96.94% for 5 mg / L BPA within 90 minutes, with a degradation rate constant of 0.0219 min. -1 The highest ferric ion leaching concentration after the reaction was 0.0728 mg / L, far below the Class I discharge limit (≤0.5 mg / L) stipulated in the National Integrated Wastewater Discharge Standard (GB 8978-1996). This catalyst maintained stable activation performance for PDS across a wide pH range of 3.0–11.0. In different water bodies (deionized water, tap water, river water, and wastewater treatment plant effluent), the catalyst achieved a total BPA removal rate of over 96%. Furthermore, this catalyst can also effectively activate PDS to degrade other novel pollutants such as BPF and BPS, demonstrating good pollutant versatility.
[0144] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing an easily recyclable three-dimensional nanoporous foam catalyst Fe2O3@N-rGF, characterized in that, Includes the following steps: Fe(NO3)3·9H2O and urea were mixed evenly to obtain an iron precursor solution, which was then mixed with a graphene oxide dispersion to obtain a mixed solution. The mixture is subjected to a one-step hydrothermal reaction; After the reaction was completed, the product was washed and dried to obtain the easily recyclable three-dimensional nanoporous foam catalyst Fe2O3@N-rGF.
2. The method for preparing the easily recyclable three-dimensional nanoporous foam catalyst Fe2O3@N-rGF according to claim 1, characterized in that, The concentration of the GO dispersion is 2 g / L.
3. The method for preparing the easily recyclable three-dimensional nanoporous foam catalyst Fe2O3@N-rGF according to claim 1, characterized in that, The concentration of Fe(NO3)3·9H2O in the iron precursor solution is 0.2 M to 0.5 M.
4. The method for preparing the easily recyclable three-dimensional nanoporous foam catalyst Fe2O3@N-rGF according to claim 1, characterized in that, The volume ratio of the GO dispersion to the iron precursor solution is (4.5~11.5):0.
5.
5. The method for preparing the easily recyclable three-dimensional nanoporous foam catalyst Fe2O3@N-rGF according to claim 1, characterized in that, The reaction temperature of the one-step hydrothermal reaction is 120~210℃, and the reaction time is 12~24 hours.
6. A recyclable three-dimensional nanoporous foam catalyst Fe2O3@N-rGF prepared by the preparation method according to any one of claims 1 to 5.
7. The application of the easily recyclable three-dimensional nanoporous foam catalyst Fe2O3@N-rGF as described in claim 6 in the degradation of organic pollutants in water by activated persulfate, characterized in that, The organic pollutant includes at least one of bisphenol A, bisphenol F, and bisphenol S.
8. The application of the easily recyclable three-dimensional nanoporous foam catalyst Fe2O3@N-rGF according to claim 7 in the degradation of organic pollutants in water by activated PDS, characterized in that, The concentration of the organic pollutants in the water is 0.5~14 mg / L.
9. The application of the easily recyclable three-dimensional nanoporous foam catalyst Fe2O3@N-rGF according to claim 7 in the degradation of organic pollutants in water by activated PDS, characterized in that, The concentration of PDS in the water is 0.3~1.8 mM.
10. The application of the easily recyclable three-dimensional nanoporous foam catalyst Fe2O3@N-rGF according to claim 7 in the degradation of organic pollutants in water by activated PDS, characterized in that, The degradation process takes place in water with a pH of 3.0 to 11.0.